2022
DOI: 10.1029/2021ja030101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of EMIC Wave‐Driven Proton Precipitation on the Ionosphere

Abstract: Particle precipitation from the plasma sheet is one important energy source for the ionosphere and plays an important role in modulating the dynamics of the ionospheric system and causing aurora (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Many studies have established the relation of EMIC waves with the proton precipitation, proton aurora, proton isotropy boundary (e.g. Jordanova et al 2001Jordanova et al , 2007Nishimura et al 2014;Yahnina and Yahnin 2014;Fuselier 2004;Chen et al 2014;Miyoshi et al 2008;Yuan et al 2010;Yahnin et al 2021;Tian et al 2022). Jordanova et al (2001) simulated the role of He-band EMIC waves in driving the ring current ions into the loss cone using the RAM-SCB model and calculating the generation of EMIC waves self-consistently with the evolving ring current distributions.…”
Section: Ion Precipitation As Another Important Energy Sourcementioning
confidence: 99%
“…Many studies have established the relation of EMIC waves with the proton precipitation, proton aurora, proton isotropy boundary (e.g. Jordanova et al 2001Jordanova et al , 2007Nishimura et al 2014;Yahnina and Yahnin 2014;Fuselier 2004;Chen et al 2014;Miyoshi et al 2008;Yuan et al 2010;Yahnin et al 2021;Tian et al 2022). Jordanova et al (2001) simulated the role of He-band EMIC waves in driving the ring current ions into the loss cone using the RAM-SCB model and calculating the generation of EMIC waves self-consistently with the evolving ring current distributions.…”
Section: Ion Precipitation As Another Important Energy Sourcementioning
confidence: 99%
“…Given such increased energy flux and mean energy of the precipitating electrons, we can expect the ionospheric conductance to be significantly enhanced. The elevated conductance could further change the electrodynamics in the magnetosphere-ionosphere system and subsequently influences the magnetospheric dynamics, as demonstrated in Zhu et al (2021) and Tian et al (2022).…”
Section: Resultsmentioning
confidence: 98%
“…EMIC wave is more important at middle latitude because it occurs mainly near the plasmapause. The pitch angle scattering of protons by EMIC waves is theoretically regarded as an important cause of proton precipitation into the atmosphere, but most of existing papers are event studies (Fuselier et al., 2004; Jordanova et al., 2007; Ozaki et al., 2021; Tian et al., 2022; Yuan et al., 2014). Our statistical results are consistent with these previous results of high‐energy proton deposition caused by magnetospheric EMIC waves but provide more significant results.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the ionospheric Ne oscillation at Swarm altitude might be relevant to the precipitating protons induced by EMIC waves. Recently, Tian et al (2022) investigated the proton precipitation caused by EMIC waves and its impact on the ionosphere with the self-consistent ring current-atmosphere interactions model coupled with an ionospheric particle transport model Global Airglow. They found that the EMIC wave diffusion process causes significant precipitation of tens of keV protons.…”
Section: Wave Effect On Nementioning
confidence: 99%